A multiple-vehicle type reactive dynamic user equilibrium model and algorithm with physical queues - ShuGuang Li (Transport, 2013)
A multiple-vehicle type reactive dynamic user equilibrium model with physical queues is presented. The single-vehicle type cumulative flow given by Newell is extended into multiple-vehicle types. The flow conditions for multiple-vehicle types on link can be divided into two classes: Class 1 is a congested condition – various types of vehicles cannot overtake; Class 2 is an uncongested condition – each type of vehicles can run according to each type of free-flow velocity. Further, multiple-vehicle type reactive dynamic user equilibrium condition is described. Finally, one iterative algorithm is proposed, and the results show that the model can demonstrate multiple-vehicle type physical queue conditions among the links and multiple-vehicle type reactive dynamic user equilibrium condition.